SNP genotypes for 6833 loci from 21 mountain hares (Lepus timidus) and 27 brown hares (Lepus europaeus) - Levänen, Riikka; Thulin, Carl-Gustaf; Spong, Göran; Pohjoismäki, Jaakko (Dryad Digital Repository, 2018)
SNP genotypes for 6833 loci from 21 mountain hares (Lepus timidus) and 27 brown hares (Lepus europaeus) from Sweden and Finland. Data sheet includes sample number, sampling location coordinates, mtDNA haplotype and notes for species co-existence at the sampling location (sympatry/allopatry).